Clinical analysis of molecular typing of 146 cases of endometrial carcinoma - Zhang, Bo; Zhou, Dan; Zhang, Shuo; Yan, Jinbowen; Meng, Qingwei; Lv, Qiubo (Frontiers in Oncology, 2025)
ObjectiveTo investigate the application of TCGA molecular typing in endometrial carcinoma, compare the relationship between molecular typing and clinicopathologic features, and provide a new idea for individual treatment of patients.MethodsA total of 146 EC patients who underwent surgical treatment and TCGA molecular typing in Beijing Hospital from December 2019 to March 2023 were collected. The clinicopathologic features, immunohistochemistry, and prognosis of the four TCGA molecular types were analyzed retrospectively.ResultAmong the 146 patients with endometrial cancer (EC), 8 patients (5.5%) exhibited the POLE hypermutant type, 29 patients (19.9%) displayed the MSI-H type, 94 patients (64.4%) presented the low copy-number type, and 15 patients (10.3%) manifested the high copy-number type. A comparative analysis of the four TCGA types and age yielded statistically significant results (p = 0.012). Notably, significant associations were observed between menopausal status, the expression of ER, PR, and the four TCGA types. However, no significant difference was observed in CA125 levels before surgery among the four TCGA types (p = 0.587). There were significant differences observed among the four TCGA types and pathological types, pathological grades, FIGO stage, lymph node metastasis, and LVSI. The progression-free survival (PFS) rates of patients with POLE hypermutation, MSI-H type, CNL type, and CNH type were 100%, 100%, 93.62%, and 73.3%, respectively. There was a statistically significant difference between the four groups(p=0.006). POLE mutant and MSI-H type patients have higher PFS, while high copy type patients have the lowest.ConclusionsTCGA molecular typing has feasibility and application value in the clinical application of endometrial cancer, and has a certain predictive effect on the prognosis of EC patients. It has a certain guiding significance for the individual treatment of patients with endometrial cancer.